Prolactin promoter gene as marker assisted selection (MAS) for the control of broodiness of Kampung chicken - Tike Sartika; S.S Mansjoer; A Saefuddin; H Martojo (Jurnal Ilmu Ternak dan Veteriner, 2004)
Preliminary research about MAS (Marker Assisted Selection) was conducted to detect broodiness trait of Kampung chicken. MAS currently is very important in situations, where the accuracy of selection is low, such as, traits with low heritability, e.g. broodiness trait and egg production. Prolactin promoter was selected as a marker gene for broodiness because it plays a critical part in the neuroendocrine cascade which is triggered at the onset of broodiness. DNA samples were collected from low and highbroodiness samples on basic population (G0) each 24 samples, and from selected population (G3) each 28 samples. As control population without broody behavior was used 16 samples White Leghorn (WL) chicken. Prolactin promoter gene was amplified using polymerase chain reaction (PCR). PCR product was analyzed using electrophoresis agarose gel 2%. The results showed four types of bands represent in the Kampung chicken, three types called as wild type band and one type as the WL band. The chickens with low and high broodiness on G0 generation have 75 and 87.5% of wild type band while in the G3 generation was decreased to 25 and 75%. Conclusions of the research indicated that the selected breed of the Kampung chicken on G3 generation increased WL band like White Leghorn chicken as much as 31,25% from the G0 generation.   Key words: Kampung chicken, prolactin promoter, MAS